Pengembangan Technology Enhanced Worksheet Inquiry (TEWI) Pada Konsep Interferensi Cahaya - Sarah, Lia Laela (Jurnal Nispatti, 2024)
In this study, a Technology Enhanced Worksheet Inquiry (TEWI) learning resource was developed as an innovative tool to support inquiry-based science learning. The first version, TEWI v1.0, was produced in two formats: a digital book in .epub format and a paper-based version equipped with QR codes to integrate digital content into printed worksheets. The implementation of TEWI v1.0 in classroom learning resulted in a normalized gain score of 59.02%, indicating that this version falls into the average effectiveness category in improving student learning outcomes. Further analysis of the worksheets shows that TEWI v1.0 provides a promising alternative to facilitate meaningful learning experiences, particularly in strengthening students’ scientific practices, inquiry processes, and intellectual skills. The integration of technology within the worksheet design also supports greater interactivity and accessibility to multimedia learning resources. However, several aspects still require improvement, especially in simplifying the explanation of concepts and refining the sense-making process to ensure better clarity for students. These findings suggest that TEWI v1.0 serves as a valuable foundational prototype, but continued development and revision are needed to optimize its pedagogical effectiveness.